TEACHING WRITING NARRATIVE TEXT USING PICTURES TO THE FIRST SEMESTER STUDENTS OF FACULTY OF SOCIAL AND POLITICS UNIVERSITY OF TULUNGAGUNG - Herminingsih, Dwi Ima (Jurnal BONOROWO, 2013)
The essential function of the language helps people sharing what they think and feel by oral or written form of language to others. Empirically and theoretically noted, the communication often fails delivering the message if the language used is not the native language of the communicators. Misunderstanding sometimes occurs not only because of the meanings of words used look unfamiliar but also the lack of ability to arrange the true sentences to express idea, thought and feeling. In the context of Indonesia, particularly at faculty of Social and Politics, University of Tulungagung, the students ‘attainment in English is not good when they are assigned to have the writing practices. Their poor mastery in vocabulary and grammar make them difficult to finish the writing tasks. Having look what happen to the students, the English teacher should be innovative to perform the teaching performance which is helpful to tackle the student’s problem. Using pictures can be a good choice to guide and ease the students to produce a well-organized writing.